Unveiling Insights: Understanding Public Knowledge, Preferences, and Perceptions of Plastic Surgery in Indonesia - Kristaninta Bangun; Teuku Fadli Nazwan Sani; Jesica Putri Sudarman; Clara Menna (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Background: Plastic surgery spans beyond aesthetics, yet public perception often limits it to cosmetic procedures. This study explores public knowledge, preferences, and perceptions of plastic surgery in Indonesia. Method: A cross-sectional study was conducted between June–July 2024 using a structured, 20-item online questionnaire covering demographics, knowledge, preferences, and perceptions. Data from 488 participants were collected and analyzed using SPSS (version 29, IBM Corp., Armonk, NY, USA). Results : A total of 488 participants were recruited; most recognized aesthetic surgery (92%), burns (85%), facial fractures (89%), and clefts (87%) as part of plastic surgery but were less aware of its role in penile reconstruction (55%) and finger amputation (38%). Most respondents rejected misconceptions about plastic surgery and expressed a high regard for appearance (89%), and 57.4% of all respondents had an aesthetic consultation. Despite this, trust in Indonesian plastic surgeons achieving global standards remained limited, with only 66% expressing trust. Conclusion: Although the Indonesian public generally aware of the basic roles of plastic surgery, significant knowledge gaps exist for specialized procedures. Despite valuing appearance, hesitation to seek services and the lack of trust in local surgeons highlight the need for public education and trust-building initiatives. The Indonesian public showed good understanding of plastic surgery, with gaps in knowledge of its more specialized procedures, and a lack of trust in local plastic surgeons.